Using Creative Making to Redesign Life After Stroke - Jennifer Fortuna (Scholarworks @ WMU, 2022)
Kate Davies, a knitwear designer and author based in Scotland, provided the cover art for the Winter 2022 edition of the Open Journal of Occupational Therapy. "Balance for Better" is a blanket made from wool and mohair. The blanket consists of 30 individual squares designed and knitted by KDD & Co. employees. The colors and pattern of each square reflect the work, achievements, and legacy of the inspirational women celebrated in the blanket. At age 36, Kate suffered a near-fatal stroke that left her paralyzed on the left side of her body. Forced to give up her career as an academic lecturer, she used the meaningful occupation of knitting to create a new path. Through knitting, Kate redesigned her life.